Some Issues in Modeling and Forecasting Inflation in South Africa. - Aron, J; Muellbauer, J (South African Reserve Bank, 2009)
This invited overview paper draws on our South African and United States (US) inflation modelling and forecasting experience. The current global crisis highlights the importance for policy-makers of having good models for forecasting inflation. Central banks’ caution about inflation risks (expressed, for example, in the Federal Reserve minutes of 16 September 2008, released on 7 October, and the European Central Bank’s 2 October 2008 statement about the decision to leave interest rates unchanged) may have been understandable, given the inflation shocks of 2008. However, it suggested the major central banks were ‘behind the curve’.